A comparison of the full and half toroidal continuously variable transmissions in terms of dynamics of ratio variation and efficiency. (March 2018) - Verbelen, Florian; Derammelaere, Stijn; Sergeant, Peter; Stockman, Kurt
Highlights: A method to compare the dynamics of a half and full toroidal CVT is proposed. The efficiency of both technologies is discussed in the complete operating range for dynamic situations. The half toroidal CVT outperforms the full toroidal CVT during ratio variation in terms of ratio variation period and efficiency. Abstract: The full and half toroidal CVT have been the subject for many research papers. The efficiency and behavior in steady state of both topologies has already been discussed in detail but until now no special attention has been given to their behavior during ratio variation. Therefore, this paper discusses the comparison of the full and half toroidal CVT during periods of ratio variation focusing on the dynamic response and efficiency. The geometrical constraints for the comparison are as follows: equal output inertia, equal maximum output torque at a speed ratio of 1 and identical radial size. The results of the study are based on a model that describes the behavior of both topologies and an algorithm that determines the optimal ratio variation. The outcome of the study shows that the half toroidal outperforms the full toroidal CVT over the entire operating range in terms of dynamics and efficiency during ratio variation.